Genome‐Wide Profiling of H3K27ac Identifies TDO2 as a Pivotal Therapeutic Target in Metabolic Associated Steatohepatitis Liver Disease - Yaling Zhu; Limeng Shang; Yunshu Tang; Qiushuang Li; Lin Ding; Yi Wang; Tiantian Zhang; Bin Xie; Jinhu Ma; Xinyu Li; Shuwen Chen; Xinrui Yi; et al. (Advanced Science)
Abstract H3K27ac has been widely recognized as a representative epigenetic marker of active enhancer, while its regulatory mechanisms in pathogenesis of metabolic dysfunction‐associated steatotic liver disease (MASLD) remain elusive. Here, a genome‐wide comparative study on H3K27ac activities and transcriptome profiling in high fat diet (HFD)‐induced MASLD model is performed. A significantly enhanced H3K27ac density with abundant alterations of regulatory transcriptome is observed in MASLD rats. Based on integrative analysis of ChIP‐Seq and RNA‐Seq, TDO2 is identified as a critical contributor for abnormal lipid accumulation, transcriptionally activated by YY1‐promoted H3K27ac. Furthermore, TDO2 depletion effectively protects against hepatic steatosis. In terms of mechanisms, TDO2 activates NF‐κB pathway to promote macrophages M1 polarization, representing a crucial event in MASLD progression. A bovine serum albumin nanoparticle is fabricated to provide sustained release of Allopurinol (NPs‐Allo) for TDO2 inhibition, possessing excellent biocompatibility and desired targeting capacity. Venous injection of NPs‐Allo robustly alleviates HFD‐induced metabolic disorders. This study reveals the pivotal role of TDO2 and its underlying mechanisms in pathogenesis of MASLD epigenetically and genetically. Targeting H3K27ac‐TDO2‐NF‐κB axis may provide new insights into the pathogenesis of abnormal lipid accumulation and pave the way for developing novel strategies for MASLD prevention and treatment.